First Efficient Two-Step/One-Pot Zirconium (IV)isopropoxide–Mediated Reductive Amination of Carbonyl Compounds - Pieri, Cyril; Michel Brunel, Jean (Letters in Drug Design & Discovery, 2015)
An efficient method for the synthesis of various primary and secondary amines through a zirconium(IV) isopropoxide–mediated reductive amination reaction of aldehydes and ketones is reported. A series of different aldehydes, ketones and amines were used leading to the expected amino products in moderate to excellent yields. The mechanistic rationale of this reaction has been postulated through the formation of a transient imine species and a diastereoselective version using (R)- phenylethylamine as chiral inducer led to the expected products in moderate to excellent yields and with diastereoselectivities up to 100%.
Keywords: Ketones